2018
DOI: 10.3390/w10010026
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Carbon Dioxide (CO2) Emissions from Reservoirs Using Artificial Neural Networks

Abstract: Freshwater reservoirs are considered as the source of atmospheric greenhouse gas (GHG), but more than 96% of global reservoirs have never been monitored. Compared to the difficulty and high cost of field measurements, statistical models are a better choice to simulate the carbon emissions from reservoirs. In this study, two types of Artificial Neural Networks (ANNs), Back Propagation Neural Network (BPNN) and Generalized Regression Neural Network (GRNN), were used to predict carbon dioxide (CO 2 ) flux emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
3
15
0
1
Order By: Relevance
“…Just as neurons in the human brain process the available information, based on past training, to arrive at intelligent solutions, artificial (and virtual) neurons are 'trained' with computers on the basis of existing data so that they can then 'intelligently' process new data and generate solutions one seeks. The ANN technique, which has been made increasingly versatile and precise over the years, has been gaining popularity due to its ability to pick up the linear or non-linear relationships among data, identify complex patterns in datasets, and make adequately accurate estimations even in situations where the number of input variables are limited [10][11][12]. Further, ANNs can be used for the mapping of input to output data without knowing a priori relationship between that data.…”
Section: The Potential Of the Artificial Neural Network (Anns)mentioning
confidence: 99%
See 2 more Smart Citations
“…Just as neurons in the human brain process the available information, based on past training, to arrive at intelligent solutions, artificial (and virtual) neurons are 'trained' with computers on the basis of existing data so that they can then 'intelligently' process new data and generate solutions one seeks. The ANN technique, which has been made increasingly versatile and precise over the years, has been gaining popularity due to its ability to pick up the linear or non-linear relationships among data, identify complex patterns in datasets, and make adequately accurate estimations even in situations where the number of input variables are limited [10][11][12]. Further, ANNs can be used for the mapping of input to output data without knowing a priori relationship between that data.…”
Section: The Potential Of the Artificial Neural Network (Anns)mentioning
confidence: 99%
“…The competence of the ANNs is further enhanced by their non-parametric nature. Due to this, the learning mechanism of the ANNs is independent of the structure of the data; hence the need for establishing prior distribution of data is obviated [12,13].…”
Section: The Potential Of the Artificial Neural Network (Anns)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has confirmed that reservoirs emit a significant amount of greenhouse gas emissions, but one of the challenges is how to accurately quantify greenhouse gas emissions from individual reservoirs. Chen et al [23] used two artificial neutral networks to estimate the total carbon dioxide emissions from the world's reservoirs and concluded that the models can be used to predict CO 2 emissions from new reservoirs.…”
Section: Reservoir Dynamics and Impactsmentioning
confidence: 99%
“…In recent reports, Deemer et al, [6]; the World Bank [1], and Chen et al [7] have emphasized the paucity of information that exists on the emission of carbon dioxide from hydroelectric and other surface water reservoirs. This has been so despite the fact that the first report on this subject had come over a quarter-century ago-in 1993 [8]-and the issue has been hotly debated ever since, remaining alive in scientific circles, as well as layperson's concerns.…”
Section: Introductionmentioning
confidence: 99%